OP25 Patients with moderate to severe Crohn's Disease with and without prior biologic failure demonstrate improved endoscopic outcomes with risankizumab: Results from phase 3 induction and maintenance trials. (21st January 2022) - Ferrante, M; Cao, Q; Fujii, T; Rausch, A; Neimark, E; Song, A; Wallace, K; Kligys, K; Zhou, Q; Kalabic, J; Feagan, B G
Abstract: Background: Risankizumab (RZB), a selective interleukin-23 inhibitor, demonstrated clinically meaningful improvements in endoscopic outcomes in patients with moderate to severe Crohn's disease (CD) during two phase 3 induction trials (ADVANCE and MOTIVATE) and the maintenance study (FORTIFY). Here, we compared the efficacy of RZB in inducing and maintaining improvements in endoscopic outcomes in patients with CD who demonstrated intolerance and/or inadequate response (IR) to biologic therapies (with prior bio-failure) versus those who demonstrated IR to conventional therapies only (without prior bio-failure). Methods: Data included in this subgroup analysis included pooled data from patients randomized to receive intravenous (IV) RZB 600mg (N=527) or placebo (PBO) IV (N=362) every 4 weeks (wks) for 12wks during induction (ADVANCE+MOTIVATE), and data from patients receiving subcutaneous (SC) RZB 360mg (N=141) or withdrawn from RZB IV to receive PBO SC (withdrawal [PBO SC], N=164) every 8wks for 52-wks during maintenance. At Wks 12 and 52, endoscopic response, endoscopic remission, ulcer-free endoscopy (absence of ulceration), and deep remission (Wk52 only) were evaluated both in the overall population and in subpopulations of patients with and without prior bio-failure. (Endpoints are defined in Table footnotes). Safety was assessed throughout the studies. Results: Approximately three-quarters of randomized patients included in this subgroup analysis had prior bio-failure (ADVANCE+MOTIVATE: 75.4%; FORTIFY: 73.8%). Higher rates of endoscopic response, endoscopic remission, and ulcer-free endoscopy were observed at Wk12 among patients receiving induction with RZB IV versus PBO IV. Subgroup analysis demonstrated treatment effects with risankizumab in patient subpopulations with and without prior bio-failure, with greater adjusted differences versus PBO in patients without prior bio-failure (Figure). At Wk52, endoscopic response, endoscopic remission, ulcer-free endoscopy, and deep remission rates favored RZB SC compared to withdrawal (PBO SC). Again, treatment effects were observed in patients with and without prior bio-failure, with greater adjusted differences versus withdrawal (PBO SC) in patients without prior bio-failure. RZB maintenance treatment was well-tolerated and no new safety signals were observed. The safety profile of RZB has been reported previously. 1, 2 Conclusion: Induction and maintenance therapy with risankizumab achieved higher rates for endoscopic endpoints in patients with moderate to severe Crohn's disease versus placebo, regardless of prior bio-failure status. However, numerically higher efficacy rates were observed in patients without prior bio-failure. 1 D'Haens, G. et al. in DDW 2021 2 Ferrante, M. et al. in UEGW 2021